2016
DOI: 10.18203/2320-1770.ijrcog20164632
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Pap smear and visual inspection with acetic acid in screening of premalignant cervical intraepithelial lesion and subclinical early cancer cervix

Abstract: Background: The objective of the study was to compare the sensitivity, specificity, positive predictive value and negative predictive value of VIA and Pap smear in screening of premalignant cervical intraepithelial lesion and subclinical early cancer cervix.Methods: An observational prospective study was done for 350 patients attending the gynecology outpatient clinic of the shatby maternity university hospital for any reasons, VIA and Pap test were done for all patients, then colposcopic guided biopsy from ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The positive predictive value, negative predictive value and accuracy were 90.5%, 74.2%, 80.6% respectively. These results were comparable to other research studies such as shown by Mustafa et al (sensitivity 77% and specificity 82%) and El Sokkary (sensitivity of 70.4%, specificity 77.6%, PPV 44% and NPV of 91.3%) 8,9 . In a meta-analysis by Sauvaget et al, data was collected from 26 studies conducted in high-and low-income countries showed a sensitivity of 80% and a specificity of 92% [10][11][12] .…”
Section: Discussionsupporting
confidence: 91%
“…The positive predictive value, negative predictive value and accuracy were 90.5%, 74.2%, 80.6% respectively. These results were comparable to other research studies such as shown by Mustafa et al (sensitivity 77% and specificity 82%) and El Sokkary (sensitivity of 70.4%, specificity 77.6%, PPV 44% and NPV of 91.3%) 8,9 . In a meta-analysis by Sauvaget et al, data was collected from 26 studies conducted in high-and low-income countries showed a sensitivity of 80% and a specificity of 92% [10][11][12] .…”
Section: Discussionsupporting
confidence: 91%
“…To address this significant public health issue; Ethiopia adopted the United Nations (UN), Sustainable Development Goal (SDG) and World Health Organization (WHO) Global Action Plan and designed the National Cancer Control Plan (NCCP). WHO recommends that early identification of premalignant lesions through visual inspection with acetic acid (VIA) and application of "screen and treat" approach can prevent invasive cervical cancer in high-risk women, and this approach is endorsed and applied by Ethiopian Federal Ministry of Health (FMOH) [4,[21][22][23][24][25]. Nowadays, achieving SDG 3.4 in the reduction of premature mortality from Non-Communicable Diseases (NCD) such as cervical cancer by 2030 is becoming a considerable government concern.…”
Section: Introductionmentioning
confidence: 99%
“…simple, reasonable price, and high sensitivity. 5,6 The Indonesian Government adopted VIA since 2014, but the coverage is still low in 2015 at 2.45%. 7 In the Special Region of Yogyakarta Province with the highest cancer prevalence in Indonesia and as the study place, the percentage of VIA test is even less than 1%.…”
Section: Introductionmentioning
confidence: 99%